UPCYCLE PENGEMBANGAN LIMBAH KANTONG SEMEN MENJADI PRODUK FASHION TAS DENGAN MENGGUNAKAN TEKNIK PEWARNAAN SUMINAGASHI: UPCYCLE DEVELOPMENT OF CEMENT BAG WASTE INTO FASHION BAG PRODUCTS USING SUMINAGASHI COLORING TECHNIQUE - Tita Gemilang; Sangayu Ketut Laksemi Nilotama; Ahadiat Joedawinata (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Upcycling is a part of the broader concept of Sustainable Development. Based on statistical data from Asosiasi Semen Indonesia (ASI), the growth of cement production capacity in the last ±5 years from 2020 to 2024 (may) has increased. Judging from the increase in cement production, more cement bag waste will be generated. This research aims to develop environmentally friendly material products with sustainable ideas that optimize the characteristics of cement bag paper waste to have functional and economic value. The product produced is a fashion item, specifically a bag. This research uses a mixed-method approach with product design methods based on design thinking, exploration, and experimentation. This research shows that cement bag waste can be made into upcycled products that have functional and economic value, one of which is made into a bag. The motif coloring technique used is the Suminagashi technique which produces unexpected elements of color and beauty and becomes an aesthetic value in the resulting motif. However, the bag products produced are not 100% environmentally friendly because there are additional complementary components in a bag